2020
DOI: 10.3390/catal10121438
|View full text |Cite
|
Sign up to set email alerts
|

Non-Thermal Plasma Coupled with Catalyst for the Degradation of Water Pollutants: A Review

Abstract: Non-thermal plasma is one of the most promising technologies used for the degradation of hazardous pollutants in wastewater. Recent studies evidenced that various operating parameters influence the yield of the Non-Thermal Plasma (NTP)-based processes. In particular, the presence of a catalyst, suitably placed in the NTP reactor, induces a significant increase in process performance with respect to NTP alone. For this purpose, several researchers have studied the ability of NTP coupled to catalysts for the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…The DBD configuration allows a suitable positioning of the catalyst very close to the discharge zone. 300 In this way, the interaction between the electric field and the catalyst surface is enhanced, and the interaction between the UV rays generated by the plasma and its oxidizing species with those generated by the catalyst generates a synergy. However, such a configuration is less suitable for a powder catalyst but is proper for a structured catalyst.…”
Section: Dbd-plasma Catalytic Systems For Wastewater Treatmentmentioning
confidence: 99%
“…The DBD configuration allows a suitable positioning of the catalyst very close to the discharge zone. 300 In this way, the interaction between the electric field and the catalyst surface is enhanced, and the interaction between the UV rays generated by the plasma and its oxidizing species with those generated by the catalyst generates a synergy. However, such a configuration is less suitable for a powder catalyst but is proper for a structured catalyst.…”
Section: Dbd-plasma Catalytic Systems For Wastewater Treatmentmentioning
confidence: 99%
“…There are different types of reactor configurations, the most used being the dielectric barrier discharge. Solid (photo)catalysts can be the introduced in various forms, as foam, honeycomb monolith, coating on the reactor walls or electrodes, or as a packed bed [55]. Different metal oxide semiconductors have been integrated in non-plasma systems, improving the degradation efficiency of emerging contaminants and thus making the process more economically sustainable [56].…”
Section: Other Heterogeneous Catalytic Processesmentioning
confidence: 99%
“…They showed that cold plasma can effectively degrade range of phenolic compounds. Another investigation on the combined effect of heterogeneous catalysts and cold plasmas for the removal and mineralization of organic pollutants from water is summarized in the critical review of Russo et al [92]. They concluded that catalysts played a significant role to enhance the performance of the plasma systems.…”
Section: Introductionmentioning
confidence: 99%